EFEKTIVITAS PERIZINAN BERUSAHA MELALUI SISTEM ELEKTRONIK TERINTEGRASI ONLINE SINGLE SUBMISSION (OSS) PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN ROKAN HULU - Rian Andrianus Manik; Mayarni Mayarni (Journal Publicuho, 2021)
AbstractOnline Single Submission is an information technology-based licensing system innovation that integrates regional and central licensing in accordance with the mandate of Government Regulation Number 24 of 2018 concerning Electronically Integrated Business Licensing Services. The purpose of this study was to determine whether the OSS program was running. The use of this OSS program is to shorten the licensing bureaucracy. This research is descriptive with a case study approach and the data needed are primary and secondary data derived from observations, interviews, and documentation which are analyzed by researchers so as to obtain accurate and clear data. The results of this study indicate that the OSS program at the Office of Investment and One Stop Services in Rokan Hulu Regency has been running effectively. The accuracy of the program targets was in accordance with the expectations set before the program was launched. The socialization of the program has not yet been effectively carried out. The achievement of program objectives is in accordance with the initial purpose of this program, the community has felt the convenience offered by OSS. Program monitoring is still not fully effective but has started to lead to improvements.Keywords: Effectiveness; Online Single Submission; Program  AbstrakOnline Single Submission merupakan inovasi sistem perizinan berbasis teknologi informasi yang mengintegrasikan perizinan di daerah dan pusat sesuai amanat Peraturan Pemerintah Nomor 24 Tahun 2018 tentang Pelayanan Perizinan Berusaha Terintegrasi Secara Elektronik. Tujuan penelitian ini adalah untuk mengetahui apakah program OSS berjalan efektif atau tidak. Penggunaan program OSS ini untuk mempersingkat birokrasi perizinan. Penelitian ini bersifat deskriptif dengan pendekatan studi kasus serta data yang diperlukan ialah data primer dan sekunder yang berasal dari observasi, wawancara, dokumentasi yang dianalisis oleh peneliti  sehingga mendapatkan data yang akurat dan jelas. Hasil penelitian ini menunjukan bahwa program OSS di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Rokan Hulu sudah berjalan efektif. Ketepan sasaran program sudah sesuai dengan harapan yang ditetapkan sebelum program ini diluncurkan. Untuk sosialisasi program masih belum efektif dilakukan. Pencapaian tujuan program sudah sesuai dengan tujuan awal program ini dibuat, masyarakat sudah merasakan kemudahan yang ditawarkan OSS. Untuk pemantauan program masih belum sepenuhnya efektif tetapi sudah mulai mengarah kepada perbaikan.    Kata Kunci:  Efektivitas; Online Single Submission; Program